The Teachers’ Efforts to Improve Reading Literacy of Third-Grade Students at SD Perti Bandar Purus Padang - Nadila Rahmawati; Ayunis Ayunis; Nofriza Efendi; Rica Azwar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The background of this study is the importance of reading skills as a foundation for knowledge acquisition and the low reading interest among students, which is evident from their lack of focus during literacy activities. This study aims to analyze the efforts of teachers in enhancing the reading interest of third-grade students at SD PERTI Bandar Purus Padang through the School Literacy Movement (GLS). The research method employs a qualitative approach using observation and interview techniques. The results indicate that the teachers' efforts to improve students' reading interest include: (1) habituating reading for 15 minutes before lessons, (2) providing an engaging reading corner, (3) collaborating with parents to support literacy activities at home, and (4) introducing various types of interesting reading materials. The implementation of GLS by teachers has proven effective in increasing students' reading interest. This study concludes that the active role of teachers in creating engaging and sustainable literacy programs is key to the success of enhancing students' literacy. Recommendations from the study include the development of a more varied collection of books and training for teachers on creative literacy techniques.